Post-exercise Hypotension Following a Single Bout of High Intensity Interval Exercise vs. a Single Bout of Moderate Intensity Continuous Exercise in Adults With or Without Hypertension: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Marçal, Isabela Roque; Goessler, Karla Fabiana; Buys, Roselien; Casonatto, Juliano; Ciolac, Emmanuel Gomes; Cornelissen, Véronique A. (Frontiers in Physiology, 2021)
Background. Post-exercise hypotension (PEH) is an important tool in the daily management of patients with hypertension. Varying the exercise parameters is likely to change the blood pressure (BP) response following a bout of exercise. In recent years, high-intensity interval exercise (HIIE) has gained significant popularity in exercise-based prevention and rehabilitation of clinical populations. Yet, to date, it is not known whether a single session of HIIE maximizes PEH more than a bout of moderate-intensity continuous exercise (MICE). Objective. To compare the effect of HIIE vs. MICE on PEH by means of a systematic review and meta-analysis. Methods. A systematic search in the electronic databases MEDLINE, Embase and SPORTDiscus was conducted from the earliest date available until February 24, 2020. Randomized clinical trials comparing the transient effect of a single bout of HIIE to MICE on office and/or ambulatory BP in humans (≥ 18 years) were included. Data were pooled using random effects models with summary data reported as weighted means and 95% confidence interval (CIs). Results. Data from 14 trials were included, involving 18 comparisons between HIIE and MICE and 276 (193 males) participants. The immediate effects, measured as office BP at 30- and 60-minutes post-exercise, was similar for a bout of HIIE and MICE (p>0.05 for systolic and diastolic BP). However, HIIE elicited a more pronounced BP reduction than MICE [(-5.3 mmHg (-7.3 to -3.3)/ -1.63 mmHg (-3.00 to -0.26)] during the subsequent hours of ambulatory daytime monitoring. No differences were observed for ambulatory nighttime BP (p>0.05). Conclusion. HIIE promoted a larger PEH than MICE on ambulatory daytime BP. However, the number of studies was small, patients were mostly young to middle-aged individuals and only few studies included patients with hypertension. Therefore, there is a need for studies that involve older individuals with hypertension and use ambulatory BP monitoring to confirm HIIE’s superiority as a safe BP lowering intervention in today’s clinical practice.